2016
DOI: 10.1158/1078-0432.ccr-15-0654
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Developmental Endothelial Locus-1 on Circulating Extracellular Vesicles as a Novel Biomarker for Early Breast Cancer Detection

Abstract: Del-1 on circulating EVs is a promising marker to improve identification of patients with early-stage breast cancer and distinguish breast cancer from benign breast tumors and noncancerous diseases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
120
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(124 citation statements)
references
References 51 publications
3
120
1
Order By: Relevance
“…Levels of MVs expressing tumor-associated proteins such as MUC1, EGFR or FAK seem to be elevated in the blood of breast cancer patients 15,16 . Also for Exos, recent studies have shown that blood-derived Exos carrying tumor-specific antigens such as Glypican-1 for pancreatic cancer or Del-1 for breast cancer allow early disease detection with high specificity and sensitivity 17,18 . Additionally, serum-derived tumor Exos may contain DNA which can be used for detection of mutations such as KRAS and p53 which suggests their use for therapy prediction 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Levels of MVs expressing tumor-associated proteins such as MUC1, EGFR or FAK seem to be elevated in the blood of breast cancer patients 15,16 . Also for Exos, recent studies have shown that blood-derived Exos carrying tumor-specific antigens such as Glypican-1 for pancreatic cancer or Del-1 for breast cancer allow early disease detection with high specificity and sensitivity 17,18 . Additionally, serum-derived tumor Exos may contain DNA which can be used for detection of mutations such as KRAS and p53 which suggests their use for therapy prediction 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their intracellular origin, exosomes work as reporters of the biochemical changes occurring in many diseases, such as cancer, neurological or immunological conditions. Many groups managed to isolate a cell-specific population of exosomes from the blood of patients [4][5][6][7][8][9][10][11] what would allow physicians to monitor in real time the status of a patient or the efficacy of a medication by simply taking a blood sample and analyzing the content of exosomes from a specific cell-type. In addition, blood draws are carried out daily in clinical practice and they have low cost in comparison to other diagnostic methods.…”
Section: Commentarymentioning
confidence: 99%
“…The antibody-based methods use a capture antibody against an exosomal marker, either coupled to streptavidin or magnetic beads [8,11], coated on the wells of an ELISA plate [5] or used in flow cytometry separation [7]. For example, circulating glypican 1-bearing exosomes have been isolated by flow cytometry and were shown to be diagnostic for early and late pancreatic cancer [7].…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations